Agreement on Overt Disseminated Intravascular Coagulation in Sepsis Patients between International Society of Thrombosis and Haemostasis Criteria and Japanese Ministry of Health and Welfare Criteria (Majalah Kedokteran Bandung, 2021)
Disseminated Intravascular Coagulation (DIC) is an acquired syndrome characterized by the activation of intravascular coagulation which is most commonly caused by sepsis. There are two types of DIC disease: overt and non-overt DICs. The International Society of Thrombosis and Haemostasis (ISTH) criteria are more frequently used in the diagnosis of overt DIC compared to Japanese Ministry of Health and Welfare (JMHW). One of the different parameters of the two criteria is the D-Dimer element in the ISTH criteria and Fibrin Degradation Products (FDP) in the JMHW criteria. The availability of fibrin-related markers is different in each health center. This study aimed to see the agreement of the DIC diagnosis based on the ISTH and JMHW criteria and to analyze the correlation between D-Dimer and FDP in sepsis patients to help clinician decide which criteria is better to use. An analytical cross-sectional study was carried out on patients with sepsis based on the clinical diagnosis from the laboratory order forms and the DIC criteria according to the ISTH and JMHW. Patients included in this study were those visiting Dr. Hasan Sadikin General Hospital Bandung from August 2019-April 2020. Data collected were analyzed statistically using Cohen's Kappa test and Spearman test, both were performed in SPSS 17.0 program.There were 35 subjects participating in this study with overt and non-overt DIC with a composition based on the ISTH and JMHW criteria of 31 and 19 vs. 4 and 16, respectively. The Kappa coefficient between ISTH and JMHW was 0.266 (p 0.021) and the correlation between the D-Dimer and the FDP was 0.88 based on the Spearman test. There is a fair agreement on the DIC diagnosis and strong correlation between the FDP and the D-Dimer in sepsis patients when assessed using the ISTH and JMHW criteria. Both criteria are equally able to assist clinicians in determining the type of DIC depending on the type of fibrin-related markers available in the health centers.
Keywords: DIC; fibrin-related markers; ISTH; JMHW; sepsis